Developing Students’ Intercultural Sensitivity at the Home Campus: An Innovative Approach Using the Theory of the Creative Action Methodology Pedagogy - van Melle, Jonathan; Ferreira, Marco (Teaching and Learning Inquiry, 2022)
Higher education institutes, including research universities and universities of applied sciences, face the challenge of developing effective internationalisation practices to prepare students for the demands of a globalising world. Researchers reporting on studies that are focused on universities’ internationalisation practices show that few practices are effective to develop students’ intercultural sensitivity. Broadly speaking, intercultural sensitivity means the ability to distinguish between real differences in values and behaviours across cultures, as well as the appreciation of values and behaviours even if they differ from one’s own. Interestingly, across the board researchers do not provide an explanation of what drives intercultural sensitivity development. This study reports on the impact of a new learning intervention that effectively developed local Dutch students’ intercultural sensitivity in the Netherlands, and it provides an explanation of this impact. For the intervention the theory of the Creative Action Methodology pedagogy (CAM) was used as a heuristic tool. CAM is a pedagogical approach that focuses on developing critical, analytical, and creative skills by having students break away from a culture of the truth. Results in this mixed-methods study, using the Intercultural Development Inventory and interviews, reveal that students significantly developed their intercultural sensitivity as they became empowered to break away from a culture of the truth.